Comparison of clinical outcomes of Lichtenstein and laparoscopic totally extraperitoneal repair techniques in inguinal hernia surgery - Kerimoğlu, Ramazan Saygın; Kargın, Süleyman; Maden, Abdullah Sami; Duyan, Abdullah Gürhan (The European Research Journal, 2025)
Objectives: This study aims to compare the clinical outcomes of open surgery (Lichtenstein procedure) with laparoscopic surgery (Totally Extraperitoneal Repair - TEP) for inguinal hernia repair. The duration of the procedure, postoperative pain, and occurrence of complications were evaluated. Methods: A retrospective research including 95 male patients was carried out from June 2023 to January 2025. Patients were classified into Lichtenstein (n=50) and TEP (n=45) groups. Demographic data, operational durations, postoperative pain evaluations (visual analog scale - VAS), return-to-work intervals, and complications were analyzed for comparison. Results: The operating duration was diminished in the TEP group, with 24±3.1 minutes for unilateral patients and 37±4.2 minutes for bilateral cases, in contrast to 46±5.3 minutes and 72±8.0 minutes in the Lichtenstein group, respectively. Postoperative pain scores were significantly decreased in the TEP group at all time intervals. The recurrence rates were low in both cohorts, recorded at 2.0% for the Lichtenstein group and 2.2% for the TEP group. The complication rates were similar, with wound infection occurring in 6% and hematoma in 4% of the Lichtenstein group, whereas seroma was noted in 4.4% of the TEP group. Conclusions: The laparoscopic TEP technique surpasses open surgery in terms of operating length and postoperative pain; yet, both methods are safe therapeutic options with low complication and recurrence rates.